Fenugreek (Trigonella foenum-graecum) plant types influenced by agro-chemicals and sulphur fertilization under different crop geometries - BOCHALIA, G S; TIWARI, R C; RAM, B; KANTWA, S R (The Indian Journal of Agricultural Sciences, 2026)
Newly identified cultivar Rmt-305 of fenugreek (Trigonella foenum-graecum L.) is determinate with synchronous maturity and wider adaptability. Therefore, to assess its adaptability with new crop geometry, agro-chemicals and sulphur fertilization in yield, yield components, quality and relative economics of fenugreek, the present investigation was formulated and conducted during 2005-06 and 2006-07 at Udaipur, India. Study was consisting of 24 treatment combinations of two plant types (Rmt-1 and Rmt-305), two crop geometries (30 cm × 10 cm and 20 cm × 15 cm), three agro-chemicals (control, thiourea @ 1000 ppm and TGA @ 100 ppm) and two levels of sulphur ( 0 and 40 kg S/ha). Results indicated that the cultivar Rmt-305 produced greater number of pods/branch (10.1), pod length (10.8 cm), number of seeds/pod (17.8), test weight (12.1 g) and harvest index (21.2%) which results in greater grain yield (1 337 kg/ha), net monetary returns (Rupees 21 250) and benefit cost ratio (2.17). The crop geometry 20 cm × 15 cm was found superior in production of yield components and yield over the crop geometry 30 cm × 10 cm and recorded the mean increase of 5.9, 5.4 and 4.1% in number of pods/branch, pod length and number of seeds/pod, respectively and results in higher grain yield (1 307 kg/ha), net monetary returns of Rupees 21 200/ha and benefit cost ratio of 2.18. Foliar sprays of thiourea and TGA significantly increased yield components, viz. number of pods/branch, pod length, number of seeds/pod and test weight and grain yield of fenugreek. The grain yield of fenugreek was increased by 11 and 10% due to foliar spray of thiourea and TGA, respectively over control. Maximum mean monetary net returns of Rupees 21 359/ha and benefit cost ratio of 2.27 were obtained with foliar sprays of TGA which was at par with thiourea and 13.70 and 11.82%, respectively higher over control. Application of sulphur @ 40 kg S/ha increased the yield components, viz. number of pods/branch, pod length, number of seeds/pod and test weight by 10.0, 7.3, 7.9 and 4.7%, respectively over control and grain yield by 16% over control. Maximum mean net monetary returns of Rupees 22 032/ha and benefit cost ratio of 2.19 were observed with sulphur fertilization. Application of agro-chemicals and sulphur significantly improved test weight, protein content and diosgenin content of seed.